Gambaran Kesulitan Belajar Siswa Serta Implikasinya Terhadap Pelayanan Bimbingan dan Konseling - Solihatun Solihatun (Jurnal Counseling Care, 2018)
ABSTRACT This study aimed to find out the description of student learning difficulties at SDN 05 Ciganjur. This research uses descriptive method with a quantitative approach. The sample of this study included all students in grades 4 and 5 of SDN 05 Ciganjur, South Jakarta who were registered in the 2016-2017 school year as many as 131 students. The data in this study were collected using PTSDL AUM as a simple and easy to express problem tool to communicate the quality and problems of students to assisting personnel (counselors). overall the score of the respondent's achievement for students' learning difficulties is in the sufficient category. Seen in the sub-variables there are three sub-variables that are in good quality, namely the sub-variables of learning skills by 77.24%, the personal sub-variables by 79.31%, and the sub-variables of the socio-emotional environment by 85.71%. The implications of the research results can be used as an analysis of students' needs for making BK programs in student learning difficulties.Keywords : Learning difficulties, Guidance and Counseling ServicesABSTRAKPenelitian ini bertujuan untuk mengetahui gambaran kesulitan belajar siswa di SDN 05 Ciganjur. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Sample penelitian ini mencakup seluruh siswa kelas 4 dan 5 SDN 05 Ciganjur  Jakarta Selatan yang terdaftar pada tahun ajaran 2016-2017 sebanyak 137 orang siswa. Data dalam penelitian ini dikumpulkan dengan menggunakan AUM PTSDL merupakan alat ungkap masalah sederhana dan mudah digunakan untuk mengkomunikasikan mutu dan masalah siswa kepada personel yang membantu (konselor). secara keseluruhan skor capaian responden untuk kesulitan belajar siswa berada pada kategori cukup. Dilihat pada sub variabel terdapat tiga sub variable yang berada pada mutu baik yaitu sub variabel keterampilan belajar sebesar 77.24%, sub variable diri pribadi sebesar 79.31%, dan sub variable lingkungan sosio-emosional sebesar 85.71%. Implikasi hasil penelitian tersebut dapat dijadikan sebagai analisis kebutuhan siswa untuk pemberian pelayanan BK dalam kesulitan belajar siswa.Kata kunci : kesulitan belajar, pelayanan bimbingan dan konseling.